The impact of improved maize germplasm on poverty alleviation: the case of Tuxpeño-derived material in Mexico - Bellon, Mauricio R.; Adato, Michelle; Becerril, Javier; Mindek, Dubravka (International Maize and Wheat Improvement Center, 2005)
This study documents how poor small-scale farmers in lowland tropical Mexico use improved maize germplasm and how this contributes to their well-being. It does this by assessing both the direct adoption of improved varieties and examining the process of their "creolization." By exposing improved varieties to their conditions and management, continually selecting seed of these varieties for replanting, and in some cases promoting their hybridization with landraces, either by design or by accident, farmers produce what they recognize as "creolized" varieties. Our key hypothesis is that poor farmers benefit from improved germplasm through creolization. Creolization provides farmers with new options, as they deliberately modify an improved technology generated by the formal research system to suit their own circumstances and needs. Different methodologies such as participatory methods, ethnography, household case studies, a household sample survey, and a collection and agronomic evaluation of maize samples were used. This study was carried out in two regions: the coast of Oaxaca and the Frailesca in the states of Oaxaca and Chiapas, two of the poorest in Mexico. While one study area is subsistence-oriented and the other commercial, in both, extreme poverty is pervasive. Maize continues to play a key role in the livelihoods of the poor in both study areas.